“I Grew Up Longing to Be What I Wasn't”: Mixed-Methods Analysis of Amerasians' Experiences in the United States and Vietnam - Lee, Sabine; McKelvey, Robert; Bartels, Susan A. (Frontiers in Political Science, 2022)
The Vietnam War left a legacy of mostly mixed-race children fathered by American (or other foreign) soldiers and born to Vietnamese mothers. These Vietnamese Amerasian children often had difficulties integrating into their post-conflict societies due to stigmatisation, and they were typically economically severely disadvantaged. This paper compares experiences of Amerasians in Vietnam with those who emigrated to the US as part of various departure programs since the end of the war in 1975. We used SenseMaker®, a mixed-methods data collection tool, to collect 377 narratives from 286 unique participants living in Vietnam and in the US exploring experiences of Amerasians in both countries. These narratives were then self-interpreted by the study participants using a questionnaire that generated a quantitative dataset. In this paper we analyse the self-coded perceptions quantitatively to determine patterns, specifically with view to investigating where experiences of Amerasians living in the US differ statistically from those living in Vietnam. This is complemented with a qualitative analysis of the accompanying narratives. Vietnamese respondents indicated more frequently that experiences were affected by economic circumstances than their US counterparts, and their identified negative experiences were significantly more strongly linked to poverty. Furthermore, Vietnamese respondents relayed that their desire to explore their biological roots was more prominent than US based participants, and they indicated more strongly than US counterparts that their biological parentage impacted their identity. In contrast, US respondents felt that their parentage impacted their physical and mental health in addition to impacting their identity, and they more strongly linked negative experiences in their narratives to their ethnicity.